Systemic immune responses after ischemic stroke: From the center to the periphery - Wu, Fan; Liu, Zongchi; Zhou, Lihui; Ye, Di; Zhu, Yu; Huang, Kaiyuan; Weng, Yuxiang; Xiong, Xiaoxing; Zhan, Renya; Shen, Jian (Frontiers in Immunology, 2022)
Ischemic stroke is a leading cause of disability and death. It imposes a heavy economic burden on individuals, families and society. Although the mortality rate of ischemic stroke has decreased with the help of drug thrombolytic therapy and an intravascular intervention. However, the nerve damage caused by ischemia-reperfusion is long-lasting. Meanwhile, this is followed by multiple organ dysfunction. In this process, the immune responses manifested by systemic inflammatory response play an important role. It begins with neuroinflammation following ischemic stroke. The large number of inflammatory cells released after activation of immune cells in the lesion area, along with the dis-activitied neuroendocrine system and autonomic nervous system, link the centre with the periphery as the invisible hand and visible hand. With the activation of systemic immunity and the emergence of immunosuppression, peripheral organs become the second battlefield of the immune response after ischemic stroke and gradually become dysfunctional. These, in turn, lead to an adverse prognosis for the patient. The purpose of this study is to probe into the systemic immune responses after ischemic stroke. We hope to provide new ideas for future research and clinical treatments to improve patient outcomes and quality of life.